2013
DOI: 10.1124/jpet.113.204933
|View full text |Cite
|
Sign up to set email alerts
|

Rolipram Attenuates Bile Duct Ligation–Induced Liver Injury in Rats: A Potential Pathogenic Role of PDE4

Abstract: Anti-inflammatory and antifibrotic effects of the broad spectrum phosphodiesterase (PDE) inhibitor pentoxifylline have suggested an important role for cyclic nucleotides in the pathogenesis of hepatic fibrosis; however, studies examining the role of specific PDEs are lacking. Endotoxemia and Toll-like receptor 4 (TLR4)-mediated inflammatory and profibrotic signaling play a major role in the development of hepatic fibrosis. Because cAMP-specific PDE4 critically regulates lipopolysaccharide (LPS)-TLR4-induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 36 publications
5
30
0
Order By: Relevance
“…Gobejishvili et al 46 and Udalov et al 47 investigated PDE4 blockade in models of cholestatic liver disease and chronic lung injury, respectively, supporting the idea that PDE4 might play a general role in chronic organ damage. In detail, cholestatic liver injury induced by bile duct ligation was accompanied by increased PDE expression.…”
Section: Discussionmentioning
confidence: 91%
“…Gobejishvili et al 46 and Udalov et al 47 investigated PDE4 blockade in models of cholestatic liver disease and chronic lung injury, respectively, supporting the idea that PDE4 might play a general role in chronic organ damage. In detail, cholestatic liver injury induced by bile duct ligation was accompanied by increased PDE expression.…”
Section: Discussionmentioning
confidence: 91%
“…Our earlier work documented that decreased cAMP levels played a causal role in the priming of monocytes/macrophages leading to an increase in LPS-inducible TNF expression [50]. We have also shown that increased cAMP signaling significantly attenuates liver inflammation, injury and development of fibrosis [59]. The results from the present study strongly indicate that Misoprostol both in vivo and in vitro is highly effective in decreasing the expression of the endotoxin-inducible pro-inflammatory cytokine, TNF, and increasing the anti-inflammatory cytokine, IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, PDE4 inhibitors have also been demonstrated to upregulate the anti-inflammtory/antifibrotic cytokine IL-10 (31-35). Recent studies have shown a pathogenic role of PDE4 enzymes in the development of cholestatic liver injury/fibrosis, and significant protection using a PDE4-specific inhibitor (36). Experimental and clinical studies provide a rationale for targeting PDE4 as a therapeutic strategy for treatment of ALD, but this has been hampered by dose-associated side effects including severe nausea, emesis, and sedative effects caused by the increased cAMP levels in the central nervous system (25, 37).…”
Section: Mechanisms Of Action Of Current Ah Therapymentioning
confidence: 99%